AKTIVITAS ANTIINFLAMASI FRAKSI ETANOL DAUN GEDI (Abelmoschus manihot L. Medik) PADA TIKUS PUTIH GALUR WISTAR - Agnis Pondinekaria Aditama (AKADEMI FARMASI JEMBER, 2017)
Gedi leaves (Abelmoschus manihot L. Medik) has been used empirically by the people of North Sulawesi to cure the disease. Flavonoids and steroids in Gedi leaves suspected to have anti-inflammatory effects. This Study aims to examine the anti-inflammatory effects of ethanol fraction from Gedi leaves (Abelmoschus manihot L. Medik) on edema of white males wistar foot induced with 1 % caragen, and to determine an effective dose of fraction to decrease the edema volume of Rat foot. The test was done using Rat Hind Paw Edeme or esthablished an artificial inflammation in left foot of white male rats. The treatments were carried out on five groups, the positive control group was administered with diclofenac sodium, the negative control group was administered with CMC Na 0,5 % solution, and the fraction groups were administered with 12 mg/Kg BB, 27 mg/Kg BB, 54 mg/Kg BB. Edema volume were measured every hour for 5 hours using a pletismometer. The average of edema volume (mL) and time (hour) were used to calculate the percentage of anti-inflammatory on each group compared to the negative control group. Obtained data were analyzed by one-way ANOVA followed by LSD test with confident level was 0,05. The result of this study indicate that gedi leaves can reduce edema volume of rat foot that induced with 1 % caragen and anti-inflammatory activity showed in ethanol fraction from Gedi leaves 12 mg/Kg BB by 55,2 %, 27 mg/Kg BB by 64,4% and 54 mg/Kg BB by 62,2%.Keywords : Daun Gedi (Abelmoschus manihot L. Medik), anti-inflammatory, edema